Supply Chain Management in Agribusiness: Efficiency and Sustainability Strategies - Amruddin Amruddin; Sadly Ashari Said; Olyvia Rosalia; Firayani Firayani; Anis Noviya (PT. Anagata Sembagi Education, 2025)
This research aims to explore the impact of Supply Chain Management on Efficiency and Sustainability Strategies within the agribusiness sector. Supply Chain Management plays a crucial role in optimizing operational processes, reducing logistical costs, and ensuring seamless product flow across various stages. This study focuses on the dual aspects of operational efficiency and environmental sustainability, examining how integrated strategies contribute to improving both profit margins and long-term ecological balance. Using a quantitative approach, data were collected from 180 respondents representing stakeholders in the agribusiness sector. Multiple linear regression analysis was employed to evaluate the relationships among variables. The findings reveal that effective Supply Chain Management significantly enhances both efficiency and sustainability, creating synergistic benefits for agribusinesses. Additionally, the study highlights the moderating role of government policies in amplifying these impacts through incentives for sustainable practices. This research contributes valuable insights for practitioners and policymakers, offering a framework to achieve competitive advantage while maintaining environmental stewardship.